2020
DOI: 10.1515/nanoph-2020-0366
|View full text |Cite
|
Sign up to set email alerts
|

Monolithic metasurface spatial differentiator enabled by asymmetric photonic spin-orbit interactions

Abstract: Spatial differentiator is the key element for edge detection, which is indispensable in image processing, computer vision involving image recognition, image restoration, image compression, and so on. Spatial differentiators based on metasurfaces are simpler and more compact compared with traditional bulky optical analog differentiators. However, most of them still rely on complex optical systems, leading to the degraded compactness and efficiency of the edge detection systems. To further reduce the complexity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…As a result, since the complex refractive index of a‐Si:H can be fine‐tuned by controlling the structural disorder of silicon‐hydrogen bonding through the deposition parameters of PECVD, in addition to the ease of fabrication and increased substrate selectivity, low‐loss a‐Si:H is a promising material to significantly improve the efficiency of silicon‐based photonic devices that could play a key role in future photonic applications. [ 51,52 ] In combination with promising design methods such as semi‐continuous metasurfaces, [ 53–55 ] deep‐learning processes, [ 56,57 ] and topological optimization, [ 58 ] low‐loss a‐Si:H is a candidate for the use in all‐dielectric metasurfaces at visible frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, since the complex refractive index of a‐Si:H can be fine‐tuned by controlling the structural disorder of silicon‐hydrogen bonding through the deposition parameters of PECVD, in addition to the ease of fabrication and increased substrate selectivity, low‐loss a‐Si:H is a promising material to significantly improve the efficiency of silicon‐based photonic devices that could play a key role in future photonic applications. [ 51,52 ] In combination with promising design methods such as semi‐continuous metasurfaces, [ 53–55 ] deep‐learning processes, [ 56,57 ] and topological optimization, [ 58 ] low‐loss a‐Si:H is a candidate for the use in all‐dielectric metasurfaces at visible frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…spin-orbit interactions (PSOIs) has been proposed to achieve spin-decoupled multifunctional metadevices by merging propagation phase and geometric phase in plasmonic metasurfaces [91] and dielectric metasurfaces. [34,35,[112][113][114] Apart from independent control of the wave front of opposite-handedness, asymmetric PSOIs can also allow independent amplitude modulation by adopting super-atoms as building blocks, [115][116][117] which may be utilized for chiral imaging and elliptical polarizers. The symmetry breaking of PSOIs is attributed to the opposite spin dependence of the propagation phase and geometric phase.…”
Section: Structures For Local Phase Modulationmentioning
confidence: 99%
“…[ 14–20 ] In comparison with the other methods, metasurface has natural advantages in miniaturization and integration of light field regulation, and it can cause spatially varying optical responses through the interaction between the light field and nanostructure instead of a spatial accumulation effect along an optical path. [ 21–26 ] Yang et al. found that a high order plasmonic vortex generated by using multi‐arm spiral nanoslits etched on metasurface carries a deuterogenic compound plasmonic vortex.…”
Section: Introductionmentioning
confidence: 99%